Peran Pembelajaran IPS dalam Menumbuhkan Kesadaran Keragaman Budaya Lokal di Sekitar Kita - Navisa Fisabilillah; Alma Pratiwi Husain (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
In the era of globalization and rapid technological advancement, Indonesia’s indigenous culture faces various challenges that may gradually erode traditional values within society, particularly among the younger generation. Local cultural diversity represents a vital national asset that must be preserved and sustained through strategic efforts, one of which is education. Social studies education plays an important role in instilling students’ knowledge, understanding, and appreciation of local cultural diversity as an essential component of national identity. This article aims to examine the contribution of social studies education to the development of students’ character through respect for cultural diversity in their surrounding environment, the cultivation of tolerance, and the enhancement of cultural awareness. The study adopts a qualitative descriptive approach using a literature review methodology by analyzing relevant academic sources, including books, journal articles, and previous research findings. The results reveal that integrating local culture and indigenous knowledge into social studies learning can strengthen students’ social awareness, deepen their understanding of cultural values, and foster responsible, empathetic, and tolerant character traits. Moreover, the effectiveness of local culture–based social studies education is strongly influenced by the role of teachers as facilitators, motivators, and role models who provide contextual, relevant, and meaningful learning experiences for students.